Monitoring changes of NDVI in protected areas of southern California - Gillespie, Thomas; Ostermann-Kelm, Stacey; Dong, Chunyu; Willis, Katherine S.; Okin, Gregory S.; MacDonald, Glen M. (Ecological indicators, 2018)
California’s Mediterranean ecosystem has been identified as one of the Earth’s biodiversity hotspots. The high degree of rapid urbanization along the southern California coastline has resulted in the loss of significant natural areas over the last century and protected areas that do exist may be further threatened by climate change, drought, and fire. We use Moderate Resolution Imaging Spectroradiometer (MODIS) sensor at a 250m pixel resolution and the Normalized Difference Vegetation Index (NDVI) to monitor temporal/spatial patterns from 2000 to 2016 within Santa Monica Mountains National Recreation Area and Channel Islands National Park. We test the hypothesis that there should be no significant long-term change in protected areas since 2000 and compare impacts of seasonality, drought, and fire. The Santa Monica Mountains National Recreation Area has experienced a long-term decline in vegetation greenness, vegetation types, and is the most significantly impacted with short-term declines during the summer with or without the impacts of fire. Change detection maps show areas of significant decline in NDVI in the Santa Monica Mountains National Recreation Area especially during the summer. The Channel Islands have relatively stable NDVI possibly due to the removal of non-native herbivores and the maritime climate around the Channel Islands may buffer some of the impacts of the regional drought. The MODIS sensors appears appropriate for identifying landscape patterns, time series, change detection maps, and the potential impacts from climate change for each park. Results suggest that all National Park landscapes and vegetation types can be inventoried at a 250m resolution and monitored at a high temporal resolution.
Gesehen am 19.05.2022